Pengetahuan dan Persepsi Masyarakat terhadap Pemanfaatan dan Konservasi Air Tanah di Kota Pekalongan - Komalawati, Komalawati; Romdon, Anggi Sahru; Hidayat, Yayat (Badan Perencana Pembangunan, Riset dan Inovasi Kota Pekalongan, 2024)
The demand for clean water in Pekalongan City is rising due to population growth, urbanization, and industrial and hotel development. The scarcity of surface water and contamination of water sources are prompting residents to turn to groundwater. However, excessive groundwater use for domestic and industrial needs could potentially lead to problems like tidal waves and floods. Despite these risks, groundwater remains a crucial source of clean water for many. This study assesses community awareness and perceptions regarding the use and conservation of groundwater. The research, conducted from July to August 2023, involved a survey, comprehensive interviews, and field observations with 200 participants. A quantitative descriptive analysis and the Chi-Square test were applied to the data. Findings reveal that while most people recognize the adverse environmental impacts of groundwater exploitation and the necessity for its conservation, insufficient government outreach has led to poor conservation practices. The study also found a positive community perception towards groundwater use and its conservation. Although only a few respondents had low awareness, their attitudes could potentially affect overall community consciousness. A significant correlation between knowledge and public perception of groundwater use and its preservation was identified, suggesting that better understanding could bolster conservation efforts. Nonetheless, enhancements in various programs, particularly those related to groundwater conservation techniques like rainwater harvesting and public water utility (PDAM) initiatives, are essential.. Keywords: Groundwater, knowledge, perception, conservation, flood